(untitled) (Research, Society and Development, 2020)
This work aimed to bring a brief outline of modern mathematics present in the textbooks of elementary school students, characterized by the evolution of mathematics teaching until today. As a proposal for teaching mathematics, a lesson plan was developed for the teaching of flat geometry for the final years of elementary school, which proposes the exhibition of objects of moments of students’ daily lives. The proposal prioritizes uniting students in their daily lives with the teaching of mathematics, which many of them create barriers to, even before knowing the content. We understand that this experience provides interaction between students to carry out activities in the classroom, in addition to understanding the importance of working with different approaches for teaching geometric content.